2019
DOI: 10.5588/ijtld.18.0822
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid for the treatment of extensively drug-resistant tuberculosis: a systematic review and meta-analysis

Abstract: SETTING: Studies have shown that linezolid (LZD) can be used to treat extensively drug-resistant tuberculosis (XDR-TB).OBJECTIVE: To conduct a systematic review and meta-analysis to assess existing evidence concerning efficacy and safety of LZD for XDR-TB treatment.DESIGN: The MEDLINE@OVID, PubMed, EMBASE, the Cochrane Library, Clinical Trials, Sinomed, CMCI, CNKI, VIP and Wanfang databases were systematically searched for randomised controlled trials, cohort studies, case series or case reports on XDR-TB pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Previous studies have demonstrated the positive association between both bedaquiline and linezolid and culture conversion in patients with MDR/RR-TB including XDR-TB [4,22,23,[26][27][28][29][30][31]. However, we additionally identified that treatment including both bedaquiline and linezolid was associated with faster sputum culture conversion when compared with treatments that only include either bedaquiline or linezolid.…”
Section: Articlementioning
confidence: 42%
“…Previous studies have demonstrated the positive association between both bedaquiline and linezolid and culture conversion in patients with MDR/RR-TB including XDR-TB [4,22,23,[26][27][28][29][30][31]. However, we additionally identified that treatment including both bedaquiline and linezolid was associated with faster sputum culture conversion when compared with treatments that only include either bedaquiline or linezolid.…”
Section: Articlementioning
confidence: 42%
“…Previous systematic reviews and meta-analyses showed that linezolid was significantly associated with higher treatment success rates and lower mortality rates among adult patients with MDR-TB. 29 , 34 All of these findings indicate that linezolid might be used to effectively treat pregnant patients with MDR-TB. However, a meta-analysis of individual participant data would be required to assess the independent association of each drug, including linezolid, with treatment success.…”
Section: Discussionmentioning
confidence: 99%
“…TB is associated with PN, and antituberculous drugs, especially isoniazid, can lead to PN 5 . In addition, with drug‐resistant TB, various second‐line treatments, such as cycloserine, ethionamide, fluoroquinolones and newer drugs (such as linezolid), can cause PN (26%) 6 . HIV is associated with PN 7 , and the concomitant treatment of HIV and multidrug resistant‐TB can result in PN in ~50% of patients 8 .…”
Section: Peripheral Neuropathy In Seamentioning
confidence: 99%